Care of elderly patients: a prospective audit of the prevalence of hypotension and the use of BIS intraoperatively in 25 hospitals in London. Issue 1 (December 2016) - Wickham, Alex; Highton, David; Martin, Daniel
Abstract Background Anaesthesia is frequently complicated by intraoperative hypotension (IOH) in the elderly, and this is associated with adverse outcome. The definition of IOH is controversial, and although management guidelines for IOH in the elderly exist, the frequency of IOH and typical clinically applied treatment thresholds are largely unknown in the UK. Methods We audited frequency of intraoperative blood pressure against national guidelines in elderly patients undergoing surgery. Depth of anaesthesia (DOA) monitoring was also audited due to the association between low DOA values and IOH with increased mortality (as part of "double" and "triple low" phenomena) and because it is a suggested management strategy to reduce IOH. Results Twenty-five hospitals submitted data on 481 patients. Hypotension varied depending on the definition, but affected 400 patients (83.3 %) using the AAGBI standard. Furthermore, 2.9, 13.5, and 24.6 % had mean arterial blood pressures <50, <60, and <70 mmHg for 20 min, respectively, and 136 (28.4 %) had systolic blood pressure decrease by 20 % for 20 min. DOA monitors were used for 45 (9.4 %) patients. Conclusions IOH is common and use of DOA monitors is less than implied by guidelines. Improved management of IOH may be a simple intervention with real potential to reduce morbidity in this vulnerable group.